2022
DOI: 10.5507/bp.2022.002
|View full text |Cite
|
Sign up to set email alerts
|

The use of biomarkers in the diagnosis and treatment of obstruction of the upper urinary tract in children

Abstract: Antenatal hydronephrosis, dilatation of the upper urinary tract (UUTD), is a common finding on prenatal ultrasound. One of the most common causes is ureteropelvic junction (UPJ) obstruction. Although such prenatally diagnosed UUTD resolves spontaneously in most newborns, further examination of these children is advocated to prevent possible irreversible kidney damage, and ultrasound is mainly used for this. If the dilatation persists or becomes symptomatic, it is necessary to proceed to other relatively demand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…This process proceeds under the influence of various enzymes, cytokines, chemokines, growth factors, signaling molecules, and genes. In recent years, several molecules have been identified that could potentially be used as biomarkers with promising results in both diagnosis and treatment, as well as a prognostic factors in children with UUTO (2). A biomarker is defined as a parameter that can be measured objectively and is evaluated as an indicator of both normal physiological and pathogenic processes and/or pharmacological responses to a therapeutic intervention (3).…”
Section: Original Papermentioning
confidence: 99%
“…This process proceeds under the influence of various enzymes, cytokines, chemokines, growth factors, signaling molecules, and genes. In recent years, several molecules have been identified that could potentially be used as biomarkers with promising results in both diagnosis and treatment, as well as a prognostic factors in children with UUTO (2). A biomarker is defined as a parameter that can be measured objectively and is evaluated as an indicator of both normal physiological and pathogenic processes and/or pharmacological responses to a therapeutic intervention (3).…”
Section: Original Papermentioning
confidence: 99%